Melanin - Blumenberg, Miroslav (IntechOpen, 2017)
The word melanin refers to dark natural pigments produced by the oxidative degradation of tyrosine, catalyzed by tyrosinase, and polymerized into insoluble granular substance. The main function of melanin is to protect from harmful agents, primarily UV radiation, but also from oxidation, heavy metals, etc. In this volume, chapters deal with production of melanin in human oral mucosa (Liviu et al.), the regulation of melanin action (Cecile et al.), production and potential technological application of fungal melanins (Pombiero-Sponchiado et al.) and an innovative method for measuring melanin in various samples (Zdybel et al.). In conclusion, this volume presents various biological and industrial aspects of melanin production, uses and analysis.